Thio-modified trianglimines, a novel group of chiral macrocyclic compounds of high structural dynamics - Natalia Prusinowska; Agnieszka Czapik; Joanna Szymkowiak; Marcin Kwit (Scientific Reports)
Abstract The embellishing of the macrocycle core with sulfur substituents of varied sterical requirements changes the structural dynamics of chiral, triangular polyimines. Despite their formal high symmetry, these compounds adopt diverse conformations, in which the macrocycle core represents a non-changeable unit. DFT calculations reveal that the mutual arrangement of sulfur-containing substituents is controlled mainly by sterical interactions. The presence of sulfur atoms affects the chiroptical properties of these compounds and causes a red shift of respective absorption bands compared to the basic trianglimine. Unexpectedly, the aromatic fragments attached to the sulfur atom have less impact on ECD spectra, visible only in particular spectral regions. Such a possibility to adapt various conformations is also seen in the crystalline phase; however, a stiff basic unit – the triangular macrocycle core – caused macrocycles’ self-assembly into columnar-like aggregates. In the crystal lattice, around the macrocycle having bulky SCPh3 groups, a space filled with solvent is formed; however, the macrocycle’s internal cavity is closed and unavailable for guest molecules. Titration of the solutions of basic SBn-substituted imine and amine macrocycles by AgOTf results in significant changes in the ECD spectra, confirming possible binding interactions between macrocycle and metal cations.